2021
DOI: 10.1108/bpmj-01-2021-0007
|View full text |Cite
|
Sign up to set email alerts
|

Do organizational citizenship behavior for the environment predict triple bottom line performance in manufacturing firms?

Abstract: PurposeOrganizational citizenship behavior for the environment (OCBE) is vital for manufacturing firms' ability to improve their triple bottom line (TBL) performance. This study's objective was to examine the direct relationship between three OCBE key dimensions, i.e. eco-initiatives (EIs), eco-civic-initiatives and eco-helping (EH) and TBL performance, i.e. economic (ECOP), social (SOP) and environmental (ENP).Design/methodology/approachThe quantitative design was used based on the positivist approach. A samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…According to SET, employees will be more willing to engage in green behavior to reciprocate the benefits if they are aware that environmental protection is an essential goal and if they feel encouraged by the company. As a result, employees can engage in green behavior at work if they believe their company values environmental sustainability alongside economic objectives that each party receives from the other in the exchange process ( Paillé et al, 2016 ; Raineri et al, 2016 ; Khan et al, 2021a , b ).…”
Section: Literature Review On Ethical Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…According to SET, employees will be more willing to engage in green behavior to reciprocate the benefits if they are aware that environmental protection is an essential goal and if they feel encouraged by the company. As a result, employees can engage in green behavior at work if they believe their company values environmental sustainability alongside economic objectives that each party receives from the other in the exchange process ( Paillé et al, 2016 ; Raineri et al, 2016 ; Khan et al, 2021a , b ).…”
Section: Literature Review On Ethical Leadershipmentioning
confidence: 99%
“…Researchers are recently interested in the role of organizational environmental sustainability, thereby encouraging employee’s green behavior at the workplace ( Norton et al, 2014 ; Stalcup et al, 2014 ; Zhou et al, 2018 ; Gurmani et al, 2021 ; Khan et al, 2021a ) However, scholars view that the hotel industry has demonstrated less emphasis on environmental issues for instance employees’ green behavior ( Okumus et al, 2019 ; Arshad et al, 2021 ; Khan et al, 2021b ). In addition, studies show that adopting green procedures and practices benefits the hospitality sector ( Gil et al, 2001 ; Blanco et al, 2009 ; Chou, 2014 ) through innovations, competitive advantages ( Goodman, 2000 ), customer satisfaction, and loyalty ( Kassinis and Soteriou, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…The company's responsibility to environmental issues must be the focus of their economic activities (Zeb et al, 2021). Sustainability is the foundation of a business strategy prioritizing the environmentally friendly business processes to achieve a better environmental sustainability performance and to gain stakeholders' trust (Hart and Dowell, 2011;Wijethilake, 2017;Pemer et al, 2020;Khan et al, 2021). Regarding spiritual capital, Zohar and Marshall (2004) stated that companies with high spiritual capital will be more sustainable because they have a better value-based vision, global concern and compassion, and long-term thinking.…”
Section: Determinants Of Environmental Sustainabilitymentioning
confidence: 99%
“…Sustainability is the foundation of a business strategy prioritizing the environmentally friendly business processes to achieve a better environmental sustainability performance and to gain stakeholders' trust (Hart and Dowell, 2011; Wijethilake, 2017; Pemer et al. , 2020; Khan et al. , 2021).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…According to research, 75% to 80% of these environmental behaviors are voluntary behaviors which can be considered as OCB for the environment (Khan, Ahmed, & Khattak, 2021). Thus, this paper investigates the effects of GHRM on EP in the pollutant industries of Pakistan with the mediation role of CSR and moderation effects of OCB.…”
Section: Introductionmentioning
confidence: 99%